The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
AIAA SCITECH 2023 Forum 2023
DOI: 10.2514/6.2023-0146
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Multidisciplinary Design Optimization of an eVTOL Aircraft using Comprehensive Analysis

Abstract: This paper presents a framework under development for enabling large-scale multi-fidelity modeling and optimization of electric vertical takeoff and landing concepts (eVTOL). The key features of the framework are a geometry-centric approach to multidisciplinary design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…For the design of a 19-seater turboprop airplane, we have compiled a dataset comprising aircraft such as Let L410 Turbolet, Dornier 228, DHC-6 Havilland Canada Twin, Beechcraft 1900, Embraer EMB-110 Bandeirante, Jetstream 32, Fairchild Metroliner III, SC7-3 Skyvan, Piper PA-42.1000 Cheyenne, Antonov An-28, and Beechcraft C99 [29][28] [27][26] [25]. In the conceptual design phase, calculations are made to determine the minimum weight of the airplane and the required fuel weight to fulfil the mission, based on mission specifications and customer requirements [30]. This meticulous process ensures that the airplane's design closely aligns with the operational needs and performance expectations established at the outset.…”
Section: Weight Estimationmentioning
confidence: 99%
“…For the design of a 19-seater turboprop airplane, we have compiled a dataset comprising aircraft such as Let L410 Turbolet, Dornier 228, DHC-6 Havilland Canada Twin, Beechcraft 1900, Embraer EMB-110 Bandeirante, Jetstream 32, Fairchild Metroliner III, SC7-3 Skyvan, Piper PA-42.1000 Cheyenne, Antonov An-28, and Beechcraft C99 [29][28] [27][26] [25]. In the conceptual design phase, calculations are made to determine the minimum weight of the airplane and the required fuel weight to fulfil the mission, based on mission specifications and customer requirements [30]. This meticulous process ensures that the airplane's design closely aligns with the operational needs and performance expectations established at the outset.…”
Section: Weight Estimationmentioning
confidence: 99%
“…A point [π‘₯ π‘˜ , 𝑦 β€² π‘˜ , πœ“ β€² π‘˜ , πœ† π‘˜ ] 𝑇 is considered sufficiently optimal in Algorithm 4 if it satisfies the following first-order optimality conditions to specified tolerances: C Β―(π‘₯, 𝑦) β‰₯ 0, πœ† β‰₯ 0, πœ† 𝑇 C(π‘₯, 𝑦) = 0, and π‘š 𝑧 = π‘‘π‘š/𝑑𝑧 = 0, (16) where C Β―(π‘₯, 𝑦) = (C(π‘₯, 𝑦), R (π‘₯, 𝑦), βˆ’R (π‘₯, 𝑦)) is the concatenated vector of all constraints in all-inequality form. It can be shown that this set of optimality conditions in an MFS algorithm is equivalent to the optimality conditions in an RS algorithm.…”
Section: Computational Convergence Conditionsmentioning
confidence: 99%
“…The motor model is based on a differentiable method [15] proposed by Cheng et al for the low-fidelity analysis of a PMSM. The motor model employed in this study was originally developed as a part of a large-scale system model of an eVTOL aircraft [16]. In our study, we maximize the efficiency of a PMSM subject to lower and upper bounds on the length and diameter of the motor.…”
Section: A Motor Optimizationmentioning
confidence: 99%
“…With the adjoint method, the cost of derivative computation scales with the number of outputs rather than the number of design variables; for optimization problems with a single objective, updating the design variables using the adjoint method is a more efficient approach (Martins and Ning, 2022;Martins and Hwang, 2013;Gray et al, 2019). This approach has been applied to efficiently optimize large systems with many degrees of freedom across various disciplines, such as topology optimization (Yan et al, 2022), aerodynamic shape optimization (Chauhan and Martins, 2021) and multidisciplinary aircraft design optimization (Sarojini et al, 2023). More recently, this approach has been applied to electric motor design; Babcock et al showed the feasibility of using adjoint-based derivative computation for motor design optimization with electro-thermal coupling (Babcock et al, 2023).…”
Section: Introductionmentioning
confidence: 99%